Geographically Weighted Regression (GWR) Model of Bandung Regency Food Security during the Covid-19 Pandemic - Muthiah Syakirotin; Tuti karyani; Trisna Insan Noor (Kadiri University - Faculty of Agriculture, 2023)
The Covid-19 pandemic has had an impact on changes in people's economic activities, leading to an increase in the poverty rate. This has an impact on people's ability to obtain safe and sufficient food. The food security status of the city/district does not always guarantee that each individual is food secure because each region has different characteristics. The diversity of each village has the effect of variance in food security results. This study aims to model the influence of the Covid-19 Pandemic and food security indicators in Bandung Regency using Geographically Weighted Regression (GWR). This research was conducted in Bandung Regency in 280 villages. The design used in this research is descriptive quantitative. The data source used was secondary data on food security in Bandung Regency. The results showed that the influence of the percentage of the population infected with Covid-19 on food security was greatest in the southern area of Bandung Regency, and the value of the Local R2 coefficient of the influence of indicators in the calculation of the food security composite was highest in Nagreg District.